An Evaluation of Nuclei Preparation of the Dormant Axillary Bud of Grapevine for Cell Cycle Analysis by Flow Cytometry - Hermawaty, Dina; Considine, John A.; Considine, Michael J. (Frontiers in Plant Science, 2022)
Whether the division of cells of a dormant meristem may be arrested, e.g., in the G1 phase, has proven to be an extremely difficult hypothesis to test. This is particularly so for woody perennial buds, where dormant and quiescent states are diffuse, and the organ may remain visibly unchanged for six to nine months of the year. Flow cytometry has been widely applied in plant studies to determine the genome size and endopolyploidy. Here we present the application of flow cytometry to measure the cell cycle status in mature dormant buds of grapevine (Vitis vinifera cv. Cabernet Sauvignon), which represent a technically recalcitrant structure. This protocol illustrates the optimisation and validation of flow cytometry data analysis to calculate the cell cycle status, or mitotic index, of dormant grapevine buds. We show how contamination with debris can be experimentally managed and give reference to the more malleable tomato leaves. We also give a clear illustration of the primary pitfalls of data analysis to avoid artefact or false results. Data acquisition and analysis strategies are detailed and can be readily applied to analyse flow cytometry data from other recalcitrant plant samples.